If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(4x + 12) = 64 Reorder the terms: 8(12 + 4x) = 64 (12 * 8 + 4x * 8) = 64 (96 + 32x) = 64 Solving 96 + 32x = 64 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-96' to each side of the equation. 96 + -96 + 32x = 64 + -96 Combine like terms: 96 + -96 = 0 0 + 32x = 64 + -96 32x = 64 + -96 Combine like terms: 64 + -96 = -32 32x = -32 Divide each side by '32'. x = -1 Simplifying x = -1
| 4.50x-3.60x=4 | | 5.7x+3=3.7x+19 | | 6x-3-8x-9=8x-14 | | 4.50x=3.60+4 | | 4.0x=3.60x+2 | | 6q-9q-3= | | 3(x+2)-3=12 | | (10x-27)*1.1x=200 | | 2n^2-4x-16=0 | | 2x+10=9x-32 | | 5x+8y=37920 | | 4.50x=4.0+2 | | (3x-6)/(7x-14) | | 8(2x-2)+10(2x+6)=24 | | 4.50x=3.55x+4 | | 6a-3=2a+4 | | 5x=15x+5000 | | 3.55x+4=4.0x+2 | | 9x-12=3x+4 | | (8-7x)/15 | | X+90=x^2 | | am*4mn*4n= | | 7y-5+2y+9=-2 | | 4n-3y+2n-8y= | | 3x^3+120x^2=-1200x | | 7y-5+2y+9= | | 3x^3+120x^2=1200x | | (2x+1)(2x^2+1)=0 | | v^2+13v+21=0 | | 6y-12/4y-8 | | 1/2x^2(3x-1)=0 | | 9x+6(3x+12)=18(3x-9) |